2021
DOI: 10.2147/idr.s333421
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacterial Biofilm Formation in Patients with Malignancy Undergoing Double J Stent Indwelling and Its Influencing Factors

Abstract: To analyze the bacterial biofilm (BF) formation in patients with malignancy undergoing double J stent indwelling and its influencing factors. Methods: A total of 167 patients with malignant tumors who received double J stent indwelling in the hospital from January 2018 to January 2021 were included in the study. The urine and double J stent samples were collected for bacterial identification and observed for BF formation on the surface of the urinary catheter under a scanning electron microscope (SEM). Univari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…After bacteria adhere to the surface of double-J tube, they can produce polysaccharide protein complex such as fibrin, lipoprotein, polysaccharide matrix on the surface of double-J tube to form a biofilm, which is called bacterial biofilm. [8][9][10] The bacterial biofilm on the double-J tube has extremely strong drug resistance and immune evasion, which is the main reason for repeated and refractory clinical infection. [8][9][10] Previous studies have shown that long-term indwelling of double-J stent is an important risk factor for recurrent urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After bacteria adhere to the surface of double-J tube, they can produce polysaccharide protein complex such as fibrin, lipoprotein, polysaccharide matrix on the surface of double-J tube to form a biofilm, which is called bacterial biofilm. [8][9][10] The bacterial biofilm on the double-J tube has extremely strong drug resistance and immune evasion, which is the main reason for repeated and refractory clinical infection. [8][9][10] Previous studies have shown that long-term indwelling of double-J stent is an important risk factor for recurrent urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…Current research suggests that the repeated urinary tract infection caused by indwelling double-J stent is mainly caused by bacterial biofilm on the surface of double-J stent. [8][9][10] Bacteria can produce polysaccharide protein complexes, such as fibrin, lipoprotein and polysaccharide matrix on the surface of double-J stent to form a biofilm, which is called bacterial biofilm. The formation of bacterial biofilm is a defense reaction for bacteria to adapt to the external environment.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations